Knowledge, attitude and practices of medical students about self-medication for acne - Talanikar, Hemant V.; Upadhye, Jayshree J. (International Journal of Research in Medical Sciences, 2019)
Background: Acne is most prevalent in adolescent girls. Self-medication for acne is most common in medical students. This study was done to evaluate the knowledge, reason, perception and pattern of self-medication for acne among undergraduate medical students. Methods: A cross-sectional study included medical students of the second phase and final phase (part I and part II). A pretested questionnaire was given to them which included questions on knowledge, attitude and practice about self-medication for acne. Results: In present study, out of 200 girls, 142 (71%) girls were affected with acne while 58 (29%) were not affected by acne. A112 (56%) girls were using allopathic medicines, 32 (16%) girls were using homeopathic medicines, 28 (14%) girls were using ayurvedic medicines while 28 (14%) girls were using other non-specific things. clindamycin was used by 104 (52%) girls, adapalene + benzoyl peroxide gel was used by 26 (13%) girls, clindamycin + nicotinamide gel was used by 12 (6%) girls, toothpaste was used by 42 (24%) girls while Aloe vera gel was used by 76 (38%) of girls. The reason for self-medication was mild nature of illness in 130 (65%) of girls, 96 (48%) girls did it to save the time, over the counter availability of medicines was the cause in 88 (44%) of girls, getting medicines from their previous prescription was seen in 52 (26%) of girls, 64 (32%) of girls did it to save the cost of consultation, 44 (22%) did it after getting knowledge from pharmacology book while 30 (15%) of girls felt embarrassed to tell their own symptoms. Conclusions: Self-medication for acne is quite high among medical students. Self-medication is part of self-care so it should be encouraged for minor illness. But should be based on thorough knowledge and restricted to over the counter drugs.